2019
DOI: 10.2341/17-302-c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Bleaching Gel Storage Temperature on Tooth Color and Sensitivity

Abstract: SUMMARY Objective: The objective of this triple-blind, split-mouth, randomized clinical trial was to evaluate the bleaching efficacy and tooth sensitivity of an in-office bleaching agent submitted to different storage temperatures (room temperature at 21.04°C±3.13°C or refrigeration at 5°C). Methods and Materials: Thirty volunteers were selected who had central incisors with color A2 or highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This sequence corroborated the patterns observed in previous studies. 42,43 Researchers had found that alteration in b* values served as the most accurate indicator of color change. 44 Conversely, another study revealed that shifts in L* values were superior indicators of tooth bleaching effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sequence corroborated the patterns observed in previous studies. 42,43 Researchers had found that alteration in b* values served as the most accurate indicator of color change. 44 Conversely, another study revealed that shifts in L* values were superior indicators of tooth bleaching effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Two researchers who were instructed in the use of the spectrophotometer were assigned to perform the color measurements. The L *, a *, and b * values of each tooth were recorded, and the average value was calculated based on three measurements per tooth 42–45 . Measurements were taken at multiple time points: baseline (T1), after the first bleaching session (T2), after the second bleaching session (T3), 1 week after the second bleaching session (T4), and 3 weeks after the second bleaching session (T5) 46 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, 14 studies were considered for eligibility. After careful examination, 10 studies were excluded because two of them did not present outcomes of interest for this systematic review, 30,31 four studies compared different commercial products, [32][33][34][35] two studies performed bleaching protocol with different full-length times, 10,36 and two studies performed the renewal of the gel in both groups 37,38 (Figure 1). Seventeen records were retrieved from other methods, but only one of them was of interest.…”
Section: Study Selectionmentioning
confidence: 99%
“…One hypothesis is that the sensitivity is caused by hydrogen peroxide molecules. These molecules diffuse through enamel and dentin, producing oxidation of tooth pigments; this chemical reaction is what provides the bleaching effect (Hortkoff, Bittencourt, Nadal, & Rezende, ). The by‐products of this reaction can reach the pulp chamber (Shackelford, Kaufmann, & Paules, ; Young, Fairley, Mohan, & Jumeaux, ) and cause serious damage to pulp tissue, especially to odontoblasts underlying dentin (Li & Greenwall, ; Moghadam et al, ; Tredwin, Naik, Lewis, & Scully, ); this may affect the regenerative potential of pulp cells, once it induces pro‐inflammatory cytokine release (Attin, Vollmer, Wiegand, Attin, & Betke, ; Soares et al, ).…”
Section: Introductionmentioning
confidence: 99%